General characteristics and therapeutic options in lung cancer in Turkey - Ozlu, Tevfik; Bulbul, Yilmaz; Arinc, Sibel; Ozyurek, Berna A.; Gunbatar, Hulya; Senturk, Aysegul; Talay, Fahrettin (European Respiratory Soc Journals Ltd, 2015)
[Abstract Not Available]
Keywords: Lung cancer / Oncology; Neoplastic diseases; Mediastinal tumour